Search for [Formula: see text] decays in [Formula: see text] collisions at [Formula: see text] = 8 TeV with the ATLAS detector - ATLAS Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2015)
A search for a massive [Formula: see text] gauge boson decaying to a top quark and a bottom quark is performed with the ATLAS detector in [Formula: see text] collisions at the LHC. The dataset was taken at a centre-of-mass energy of [Formula: see text] and corresponds to [Formula: see text] of integrated luminosity. This analysis is done in the hadronic decay mode of the top quark, where novel jet substructure techniques are used to identify jets from high-momentum top quarks. This allows for a search for high-mass [Formula: see text] bosons in the range 1.5-3.0 [Formula: see text]. [Formula: see text]-tagging is used to identify jets originating from [Formula: see text]-quarks. The data are consistent with Standard Model background-only expectations, and upper limits at 95 % confidence level are set on the [Formula: see text] cross section times branching ratio ranging from [Formula: see text] to [Formula: see text] for left-handed [Formula: see text] bosons, and ranging from [Formula: see text] to [Formula: see text] for [Formula: see text] bosons with purely right-handed couplings. Upper limits at 95 % confidence level are set on the [Formula: see text]-boson coupling to [Formula: see text] as a function of the [Formula: see text] mass using an effective field theory approach, which is independent of details of particular models predicting a [Formula: see text] boson.